Pengaruh Kepemilikan Keluarga terhadap Penghindaran Pajak dengan Pengungkapan Corporate Social Responsibility sebagai Variabel Moderasi - Putri, Fania Rahayu; Helmy, Herlina (Jurnal Eksplorasi Akuntansi, 2025)
This study examines the impact of family ownership on tax avoidance, with corporate social responsibility disclosure serving as a moderating variable. A quantitative research design was employed, utilizing secondary data obtained from manufacturing firms with family ownership listed on the Indonesia Stock Exchange (IDX) during the period 2021 to 2023. The sample was selected using a purposive sampling technique, resulting in 91 observational data points. Hypothesis testing was conducted through Moderated Regression Analysis (MRA) using SPSS version 30. The findings indicate that family ownership has no significant effect on tax avoidance, and CSR disclosure does not moderate the relationship between family ownership and tax avoidance.